MUHAMMAD ASAD'S DESIGN OF AN ISLAMIC STATE IN POST-COLONIAL PAKISTAN - Amir, Ahmad Nabil (UIN Raden Mas Said Surakarta, 2024)
The paper aims to highlight Muhammad Asad’s epistemological postulate on Islamic politics as reflected in his works on Islamic state. It seeks to address these fundamental problems: what is the legal basis that support and establish Asad’s position of founding an Islamic state? and how could this idea fairly accommodates with the prevailing notion of nation state in post-colonial context. Thus, the study set forth to find the answers based on such range of objectives: to analyse the underlying ideas of Islamic state as advocated in the classical sources, to define the basic constitutional framework as developed by Asad in the context of historical Pakistan, to estimate the implication of implementing Islamic law and its impact on the global politics and its compatibility with international law. In this regards, Asad had formulated the constitutional ideas of Islamic state whose constitution contains the provision of Islamic law that practiced and implemented the norms stated in the Divine Writ. This ideas was partly enshrined in the Pakistan constitutional law whose political establishment was formed in 1947. The paper essentially discussed Muhammad Asad’s political ideas and its underlying philosophy as espoused in his works. The study conducted based on qualitative approaches of the type of library research. The data were analysed by way of descriptive, analytical and comparative technique. The finding shows that Muhammad Asad had formulated comprehensive theoretical framework of legal aspect of Islamic governance drawn up from the fundamental principle and doctrine of the shariah, and its moral norms deriving from the explicit Qur’anic and sunnah text, while also advocating democratic ideals and principles based on conventional practice and requirement of modern context of nation state. Based on this main finding, it is concluded that Islamic teaching and its spiritual norms were compatible with democratic ideal and values of human right, participatory and constitutional government as implemented in the democratic space of Pakistan.